Design and formative evaluation of the Policy Liaison Initiative: a long-term knowledge translation strategy to encourage and support the use of Cochrane systematic reviews for informing health policy. (25th January 2016) - Brennan, Sue E; Cumpston, Miranda; Misso, Marie L; McDonald, Steve; Murphy, Matthew J; Green, Sally E
Abstract : The Policy Liaison Initiative (PLI) is a long-term knowledge translation initiative designed to support the use of Cochrane systematic reviews in health policy. A joint initiative between the Australasian Cochrane Centre and Australian Government Department of Health and Ageing, the PLI includes: 1) a community of practice for evidence-informed policy, 2) skill building workshops, and 3) a website and summaries of policy-relevant reviews. This paper describes the development of the initiative and reports the findings of a formative evaluation, using interviews with policy makers and qualitative analysis to investigate perceptions of the PLI and its potential to enable research use.